"What Counts" as Research? Comparing Policy Guidelines to the Evidence Education Leaders Report as Useful. (February 2022) - Farrell, Caitlin C.; Penuel, William R.; Davidson, Kristen
Despite calls for evidence-based decision making, the field has a limited understanding of how educational leaders actually engage research. This study draws on a nationally representative sample of 368 district and school leaders who named pieces of research that were useful to their work. Educational leaders found frameworks and practical guidance in the form of books to be most useful. They report turning to research across different domains of leadership practice, including supporting their own professional learning, guiding instructional activities for others, and monitoring and supporting implementation. While a small portion of sources named would qualify for the top three "tiers of evidence" of the Every Student Succeeds Act, those sources named as useful for program selection more frequently met these criteria. Together, these findings offer a broader portrait of research use, one rooted in leaders' engagement with research as a part of their multifaceted and complex practice.